The Growth of Political Organizations During the Dutch Colonial Period - Bella, Sinta; Sembiring, Marselinus Eprimsa; Sinaga, Rosmaida (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Political organizations engaged in politics were a bonus to the ethical politics run by the colonial government. The emergence of educated elites opened up space for the movement towards an independent Indonesia and freedom from colonialism. In accordance with the purpose of writing, namely to find out the background of the emergence of political organizations, what were the political organizations during the colonial period and what influences resulted from the existence of these political organizations. The method used in the research is descriptive research based on literature study. With the results of his research, the background of the formation of political organizations is the emergence of an elite group of students who are not only from the nobility but have been evenly distributed due to easy access to education as a manifestation of ethical politics. These organizations include the Indische Partij, the Indonesian Association and the Indonesian Communist Party, as well as other political organizations. These political organizations have an influence on society, namely they have a forum for struggling to carry out movements, such as publishing writings in magazines that can be read by the public, speaking at forums both locally and internationally. The movements they carried out often made the Dutch worried so that inevitably the organization was limited and even disbanded.